2017
DOI: 10.3389/fpsyg.2017.02020
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Multi-Dimensional Scale of Perceived Social Support in Chinese Parents of Children with Cerebral Palsy

Abstract: The Multi-dimensional Scale of Perceived Social Support (MSPSS) is one of the most extensively used instruments to assess social support. The purpose of this research was to test the reliability, factorial validity, concurrent validity and measurement invariance across gender groups of the MSPSS in Chinese parents of children with cerebral palsy. A total of 487 participants aged 21–55 years were recruited to complete the Chinese MSPSS and Parenting Stress Index-Short Form (PSI-SF). Composite reliability was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 39 publications
8
36
0
1
Order By: Relevance
“…Regarding the reliability analysis, our statistical results supported that every construct in the scale being reliable. This was similar to results of a study of Chinese parents of children with cerebral palsy [21] and supported all three of the subscales achieving very good reliability values. The scale also demonstrated good internal consistency reliability with CR values of >0.7; therefore, the scale is considered a reliable and valid tool to measure social support as perceived by adolescent disaster survivors.…”
Section: Plos Onesupporting
confidence: 88%
See 3 more Smart Citations
“…Regarding the reliability analysis, our statistical results supported that every construct in the scale being reliable. This was similar to results of a study of Chinese parents of children with cerebral palsy [21] and supported all three of the subscales achieving very good reliability values. The scale also demonstrated good internal consistency reliability with CR values of >0.7; therefore, the scale is considered a reliable and valid tool to measure social support as perceived by adolescent disaster survivors.…”
Section: Plos Onesupporting
confidence: 88%
“…MSPSS in samples of undergraduate men and women and reported that both the configural and metric tests were fully invariant, while its metric equivalence was partially invariant. Our study also obtained similar results from a recent study conducted in Chinese parents of children with cerebral palsy in which the MSPSS held the same constructs across gender groups [21]. Our findings described how the structure of the Indonesian version of the MSPSS measures similar constructs and item contents for both male and female adolescent disaster survivors.…”
Section: Plos Onesupporting
confidence: 85%
See 2 more Smart Citations
“…The scale has acceptable reliability and validity in Chinese (Y. Wang, Wan, Huang, Huang, & Kong, 2017).…”
Section: Social Supportmentioning
confidence: 96%